Identification and characterization of a small molecule BFstatin inhibiting BrpR, the transcriptional regulator for biofilm formation of Vibrio vulnificus - Lee, Hojun; Hwang, Seung-Ho; Shin, Hyunwoo; Ha, Nam-Chul; Wang, Qiyao; Choi, Sang Ho (Frontiers in Microbiology, 2024)
Many pathogenic bacteria form biofilms that are resistant to not only host immune defenses but also antibiotics, posing a need for the development of strategies to control biofilms. In this study, to prevent biofilm formation of the fulminating foodborne pathogen Vibrio vulnificus, chemical libraries were extensively screened to identify a small molecule inhibiting the activity of BrpR, a transcriptional regulator for biofilm genes. Accordingly, the BrpR inhibitor BFstatin [N1-(2-chloro-5-fluorophenyl)-N3-propylmalonamide], with a half-maximal effective concentration of 8.01 μM, was identified. BFstatin did not interfere with bacterial growth or exhibit cytotoxicity to the human epithelial cell line. BFstatin directly bound to BrpR and interrupted its binding to the target promoter DNAs of the downstream genes. Molecular dynamics simulation of the interaction between BFstatin and BrpR proposed that BFstatin modifies the structure of BrpR, especially the DNA-binding domain. Transcriptomic analyses revealed that BFstatin reduces the expression of the BrpR regulon including the cabABC operon and brp locus which contribute to the production of biofilm matrix of V. vulnificus. Accordingly, BFstatin diminished the biofilm levels of V. vulnificus by inhibiting the matrix development in a concentration-dependent manner. Altogether, BFstatin could be an anti-biofilm agent targeting BrpR, thereby rendering V. vulnificus more susceptible to host immune defenses and antibiotics.